Komodifikasi Kata-kata Kasar di Channel YouTube Tekotok - Hidayatullah, Muhammad Fahmi; Rohimi, Primi (Prodi KPI FDPM IPMAFA Bekerjasama dengan Mafa Press IPMAFA Pati, 2025)
The commodification of abusive language on the YouTube channel Tekotok is an intriguing phenomenon to study, given its impact on communication behavior in society, particularly among adolescents. This research aims to identify the forms of abusive language used in Tekotok's content and analyze its social and psychological effects on the audience. The research method employed is a qualitative approach with data collection techniques through observation and content analysis of video materials. Data were collected from ten selected videos on the Tekotok channel that contain elements of abusive language. The results indicate that there is a variety of abusive language usage that serves as a tool to attract attention, create humor, and convey social criticism. However, the impacts also include the normalization of abusive language use among adolescents, which can lead to decreased empathy and increased aggressive behavior. The conclusion of this study emphasizes the importance of awareness regarding the negative effects of using abusive language in social media and the need for education on more positive communication.